Interspecies-cooperations of abutilon theophrasti with root colonizing microorganisms disarm BOA-OH allelochemicals. (3rd August 2017) - Schulz, Margot; Sicker, Dieter; Schackow, Oliver; Hennig, Lothar; Yurkov, Andrey; Siebers, Meike; Hofmann, Diana; Disko, Ulrich; Ganimede, Cristina; Mondani, Letizia; Tabaglio, Vincenzo; Marocco, Adriano
ABSTRACT: A facultative, microbial micro-community colonizing roots of Abutilon theophrasti Medik. supports the plant in detoxifying hydroxylated benzoxazolinones. The root micro-community is composed of several fungi and bacteria with Actinomucor elegans as a dominant species. The yeast Papiliotrema baii and the bacterium Pantoea ananatis are actively involved in the detoxification of hydroxylated benzoxazolinones by generating H2 O2 . At the root surface, laccases, peroxidases and polyphenol oxidases cooperate for initiating polymerization reactions, whereby enzyme combinations seem to differ depending on the hydroxylation position of BOA-OHs. A glucosyltransferase, able to glucosylate the natural benzoxazolinone detoxification intermediates BOA-5- and BOA-6-OH, is thought to reduce oxidative overshoots by damping BOA-OH induced H2 O2 generation. Due to this detoxification network, growth of Abutilon theophrasti seedlings is not suppressed by BOA-OHs. Polymer coats have no negative influence. Alternatively, quickly degradable 6-hydroxy-5-nitrobenzo[ d ]oxazol-2(3 H )-one can be produced by the micro-community member Pantoea ananatis at the root surfaces. The results indicate that Abutilon theophrasti has evolved an efficient strategy by recruiting soil microorganisms with special abilities for different detoxification reactions which are variable and may be triggered by the allelochemical´s structure and by environmental conditions.